Taxonomic study of the genus Cephalispa Malloch of Japan (Diptera: Muscidae) - Yoshizawa, Satoshi; Tachi, Takuji (Zootaxa, 2016)
Japanese species of the genus Cephalispa Malloch, 1935 are revised. Cephalispa kudoi sp. nov., C. okinawaensis sp. nov. and C. triquetra sp. nov. are described. Lispocephala xanthogaster (Shinonaga, 2003) is transferred to the genus. A key to Japanese species is provided.